Clinical characteristics of child and adolescent psychiatric outpatients engaging in fireplay or arson: a case-control study - Yoshinori Sasaki; Yuki Hakosima; Kumi Inazaki; Yuki Mizumoto; Takayuki Okada; Katsunaka Mikami; Noa Tsujii; Masahide Usami (BMC, 2023)
Abstract Background Fireplay and arson incidents among children and adolescents have gained attention because of their potentially severe consequences and societal impacts. Understanding the underlying psychiatric characteristics of individuals engaging in fireplay or arson is crucial for early identification and targeted intervention. However, there is a lack of research conducted in clinical psychiatric populations in this context. This study compared the clinical characteristics of child and adolescent psychiatric outpatients who engaged in fireplay or arson with those without such behaviors. Methods A retrospective case-control study was conducted using data collected from patients who visited the Department of Child and Adolescent Psychiatry at Kohnodai Hospital, National Center for Global Health and Medicine in Japan, between April 2014 and March 2022. Medical records were checked to see if the patient had practically committed behaviors that corresponded to fireplay or arson. The case group was identified using this process. After identifying the case and control groups, sex, diagnosis, antisocial behavior, abuse history, and children-to-parent violence were assessed and compared by careful review of medical records. Results The study identified 64 patients who engaged in fireplay or arson, representing approximately 1.1% of the total 5,587 patients (case group). The median age of the patients' first fire-related behavior was 13 years (range, 6-18 years). In the case group, 14.1% of the cases involved arson, resulting in substantial damage. Of the remaining 5523 patients, 2268 patients had datasets for the first consultation (control group). The most prevalent diagnosis in the case group was attention-deficit hyperactivity disorder (ADHD), present in 57.8% of the cases. The study revealed a significant association between fire-related behaviors and ADHD as well as antisocial behavior. Gender differences were observed, with boys being more likely to engage in fireplay or arson than girls. Conclusions This study suggests that clinicians and mental health professionals should closely consider male sex, ADHD, and antisocial behaviors as potential risk factors for fire-related behaviors. Monitoring the case group for the development of psychiatric disorders, including the use of illegal drugs, is recommended to prevent future arson incidents.